Metals and metalloids in high‑altitude Pyrenean lakes: sources and distribution in pre‑industrial and modern sediments - Rodriguez‑Iruretagoiena, Azibar; Gredilla, Ainara; Fdez‑Ortiz de Vallejuelo, Silvia; Arana, Gorka; Meaurio, Maite; Madariaga, Juan Manuel; Auguet, Jean Christophe; González, Aridane González; Pokrovsky, Oleg S.; Camarero, Luis; Diego, Alberto de (Environmental science and pollution research)
High-altitude Pyrenean lakes are ecosystems far from local pollution sources, and thus they are particularly sensitive to the atmospheric deposition of metals and metalloids. This study aims to quantify the effect of human activity in 18 lakes located in both side of the France–Spain frontier. Sediment cores were collected in summer 2013, sampled at a 1cm resolution and the concentration of 24 elements was measured by ICP-MS. Statistic and chemometric analysis of the results highlights the influence of the geographical position and lithogenic features of each lake basin on trapping pollutants. More than the 80% of the lakes showed values of enrichment factor (EF) above 2 for at least one of the elements investigated in at least one core interval, which corroborates the existence of historical anthropogenic inputs of elements in the studied area. The results demonstrate the natural origin of As and Ti in Pyrenees, together with the significant anthropogenic inputs of Cd, Pb, Sb and Sn from ancient times. The data set points mining activities as the main historical source of pollution and illustrate the large impact of the industrial revolution. The regional variability could reflect also differential long-range transport, followed by dry or wet deposition.